Book review: Women in the Irish Film Industry. Stories and Storytellers. Liddy, Susan, 2020. Cork: Cork University Press. 258 pp., £28.67 (hardback), ISBN: 978-1-78205-373-6 - Murphy, Ciara L. (Irish Journal of Arts Management and Cultural Policy, 2024)
In Women in the Irish Film Industry. Stories and Storytellers (Cork University Press, 2020), editor Susan Liddy and contributors present an informed and comprehensive analysis of women’s roles and participation in the Irish film and screen industries. This collection is an important account of the gendered aspects of Irish culture, negotiating, through its seventeen chapters and contributors, the intersecting cultural, social, and artistic dynamics of a changing and changeable Ireland. In her introduction to the volume, Liddy acknowledges the importance of reclaiming hidden and oppressed histories, noting that ‘the processes and practices that can foster and normalise such exclusion are important to excavate, analyse, and challenge’ (Liddy, 2020, p. 1), something this collection does carefully and comprehensively. The research represented in this volume is timely and necessary, and gestures towards the need for future research. This volume provides a multitude of starting points for thoughtful interrogation and presents a visible map towards future research.